1993
DOI: 10.1038/bjc.1993.282
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cytokine production in whole blood cell cultures of patients with gynaecological carcinomas in different clinical stages

Abstract: Summary The production of the cytokines IFN-gamma, IL-1-alpha, IL-2 and TNF-alpha was investigated in mitogen-stimulated, whole blood cell culturs from 239 untreated patients with primary gynaecological carcinomas (breast, cervix, ovary, endometrium), and 191 healthy female controls.The cytokines were measured in the 4-day post-inductional supernatants by a sensitive enzymoimmunological assay. In the blood cell cultures of all four groups of cancer patients, significantly lower values of IFN-gamma (P < 0.001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…A perturbation of the cytokine network characterised by low levels of IL-12 and normal or high levels of IL-10 has been previously reported in patients with neoplasms of various organs (O'Hara et al, 1998;Jacobs et al, 1998;Merendino et al, 1999); it has been suggested that this imbalance in IL-12 and IL-10 levels could explain the shift from type 1 to type 2 cytokine production by T lymphocytes known to occur in cancer patients (Elässer-Beile et al, 1993;Clerici et al, 1994;Clerici et al, 1997Clerici et al, , 1998. Actually, we found that T-helper lymphocytes from our cancer patients were polarised towards the Th2 phenotype, suggesting that altered production of regulatory cytokines by DCs may affect adaptive immune responses.…”
Section: Discussionmentioning
confidence: 78%
“…A perturbation of the cytokine network characterised by low levels of IL-12 and normal or high levels of IL-10 has been previously reported in patients with neoplasms of various organs (O'Hara et al, 1998;Jacobs et al, 1998;Merendino et al, 1999); it has been suggested that this imbalance in IL-12 and IL-10 levels could explain the shift from type 1 to type 2 cytokine production by T lymphocytes known to occur in cancer patients (Elässer-Beile et al, 1993;Clerici et al, 1994;Clerici et al, 1997Clerici et al, , 1998. Actually, we found that T-helper lymphocytes from our cancer patients were polarised towards the Th2 phenotype, suggesting that altered production of regulatory cytokines by DCs may affect adaptive immune responses.…”
Section: Discussionmentioning
confidence: 78%
“…It is thought to reflect defective tumor immunity in patients with solid tumors [30, 31]. Accordingly, tumor regression has been observed after treatment with IL-2 [32].…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 and TNF-a are shown in Table 1. Others have pointed out a potential decrease in cytokine levels with an increase in age (Elsasser-Beile et al 1993a). However.…”
Section: Cytokine Secretion In Whole Blood Cell Cultures Of Normal Inmentioning
confidence: 99%
“…including our ow-n. have reported selective changes in the cvtokine profile secreted by lymphocytes and monocytes of carcinoma patients (Rev et al 1983: Elsasser-Beile et al 1993a.b: Fischer et al 1995: De Groote et al 1996. Such a reduction might at least in part occur as a consequence of soluble immunosuppressix e factors that are released bv tumour cells (Ebert et al 1990: Fischer et al 1994).…”
mentioning
confidence: 99%